CIRI-CIRI UALAMA SEJATI, KEDUDUKAN DAN KEMULIAANNYA (CHARACTERISTICS OF THE TRUE UALAMA, POSITION AND ITS GLORY) - eliyah arhadi arhadi (J-MD Jurnal Manajemen Dakwah, 2021)
Ulama are people who are at their peak, when they are young, forging themselves to obtain and achieve noble adab which is recognized by the Shari'a and their dignity and reason, and their opinions and speech agree to praise them as civilized people. They are the experts of science who occupy the pinnacle of nobility and glory, reach the baton of the pioneers of knowledge which is the legacy of the Prophets. The following is the position of scholars in Islam: 1. The advantages of a pious compared to a worship expert are such as the virtue of the moon on a full moon night over all the stars. The scholars are the inheritors of the prophets, and the prophets did not inherit the dinar and dirhams, they only inherited knowledge. 2. The virtues that Allah has promised to the scholars are: Allah SWT will provide his sustenance, Allah will make his affairs easy, and Allah will make the path easy to heaven. 3. The following are the criteria for true scholars: 1. Feeling controlled by Allah, calm and dignified. 2. Maintain knowledge. 3. Zuhud. 4. Glorify knowledge by not making it a rung to reach the interests of the world. 5. Avoid humble jobs and stay away from sources of accusations. 6. Maintain the Zahir symbols of Islam and reveal the Sunnahs. 7. Maintain matters recommended in the syari'at-syariat. 8. Associating with humans with noble morals. 9. Purifying the mind and being born of despicable morals and filling it with commendable morals. 10. Try earnestly and always want to add to the good. 11. Not refusing to take advantage of others even if he is under it. 12. Write at the time has the capacity to write.